Memorials of Rev. Carstairs Douglas, M.A., LL.D., missionary of the Presbyterian Church of England at Amoy, China - Douglas, Carstairs (Waterlow, 1877)
Notes of his life, education and training, objects, habits, and work, by one of his brothers -- Extracts from correspondence, memorials from associates, and other writings